2005
DOI: 10.1242/dev.01918
|View full text |Cite
|
Sign up to set email alerts
|

A genetic screen in zebrafish identifies the mutantsvps18, nf2andfoie grasas models of liver disease

Abstract: Hepatomegaly is a sign of many liver disorders. To identify zebrafish mutants to serve as models for hepatic pathologies, we screened for hepatomegaly at day 5 of embryogenesis in 297 zebrafish lines bearing mutations in genes that are essential for embryonic development. Seven mutants were identified, and three have phenotypes resembling different liver diseases. Mutation of the class C vacuolar protein sorting gene vps18results in hepatomegaly associated with large, vesicle-filled hepatocytes,which we attrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
164
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 60 publications
3
164
0
Order By: Relevance
“…A screen in zebrafish by using retroviral insertional mutagenesis identified nearly 1/4 of the genes that are essential for embryogenesis, and the mutated gene has been identified in every line (21). Streptavidin linked to the fluorophore CY3 (CY3-SA) effectively labels the liver in fixed embryos and was used to screen 294 of these lines for mutants with liver size defects (30), and the hi 272 was chosen for further analysis. Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A screen in zebrafish by using retroviral insertional mutagenesis identified nearly 1/4 of the genes that are essential for embryogenesis, and the mutated gene has been identified in every line (21). Streptavidin linked to the fluorophore CY3 (CY3-SA) effectively labels the liver in fixed embryos and was used to screen 294 of these lines for mutants with liver size defects (30), and the hi 272 was chosen for further analysis. Fig.…”
Section: Resultsmentioning
confidence: 99%
“…21. CY3-SA staining was performed as described (30). Mutants that were healthy on day 5 and had little or no liver tissue staining with CY3-SA were scored as small-for-size liver mutants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Larvae have started to be used in genetic and chemical screenings for the development of drugs targeting obesity (Jones et al 2008, Chu et al 2012, and NAFLD and NASH have been reported in various fish models (Asaoka et al 2013). For example, fgr mutant (Sadler et al 2005) and transgenic zebrafish expressing the hepatitis B virus X protein (Shieh et al 2010) display most of the mammalian NASH features. Furthermore, NAFLD can be induced in healthy zebrafish both chemically, with tamoxifen (Anezaki et al 2009), and with a high-fat content diet (Oka et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Several proteins are responsible for liver metabolism, including uncoupling protein 2, phosphoenolpyruvate carboxykinase (pck1) and carnitine palmitoyltransferase 1A (Gut et al 2013). Staining with Oil Red O allows to detect adipocytes close to the gut and pancreas of zebrafish (Sadler et al 2005). Intestinal lipids can also be observed in vivo using fluorescently labelled fatty acid analogues (Farber et al 2001).…”
Section: Metabolic Diseasesmentioning
confidence: 99%